Dose–Response Curve in REMA Test: Determination from Smartphone-Based Pictures - Eugene B. Postnikov; Alexander V. Sychev; Anastasia I. Lavrova (Analytica)
We report a workflow and a software description for digital image colorimetry aimed at obtaining a quantitative dose–response curve and the minimal inhibitory concentration in the Resazurin Microtiter Assay (REMA) test of the activity of antimycobacterial drugs. The principle of this analysis is based on the newly established correspondence between the intensity of the <semantics>a*</semantics> channel of the CIE L*a*b* colour space and the concentration of resorufin produced in the course of this test. The whole procedure can be carried out using free software. It has sufficiently mild requirements for the quality of colour images, which can be taken by a typical smartphone camera. Thus, the approach does not impose additional costs on the medical examination points and is widely accessible. Its efficiency is verified by applying it to the case of two representatives of substituted 2-(quinolin-4-yl) imidazolines. The direct comparison with the data on the indicator’s fluorescence obtained using a commercial microplate reader argues that the proposed approach provides results of the same range of accuracy on the quantitative level. As a result, it would be possible to apply the strategy not only for new low-cost studies but also for expanding databases on drug candidates by quantitatively reprocessing existing data, which were earlier documented by images of microplates but analysed only qualitatively.